Draft Annual Plan 2004-2005 (Sectoral Plans) Volume-I Government of Nagaland - Planning Commission (Planning Commission, 2004)
The progress made for the various programmes under Crop Husbandry, Research & Education, Agricultural Marketing and Plantation Crops are quite satisfactory as of now. the physical target during 2003-04 is likely to achieve above 80% as the assessment is still under progress.